Membentuk Jiwa Kewirausahaan Sejak Dini Melalui Edukasi Berbisnis Untuk Beramal Di Panti Asuhan Bahagia - Jasri, Jasri; Nuraini, Nuraini (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This community service activity aims to foster a spirit of social entrepreneurship from an early age through the delivery of educational material titled “Doing Business for Charity” to the children of Panti Asuhan Bahagia (Bahagia Orphanage). The activity was motivated by the lack of structured social entrepreneurship programs in the orphanage, resulting in the children often being passive recipients of donations. The method used was participatory and educational with an Islamic value-based approach, implemented through interactive material presentation and the awarding of certificates of appreciation. Evaluation was conducted through direct observation and brief interviews to assess participant engagement, understanding, and responses. The results showed an increase in understanding of the social business concept, enthusiasm, social awareness, and appreciation of Islamic entrepreneurial values. This activity had a positive impact on character building and can serve as an effective community service model for developing social entrepreneurship among orphanage children